Speaking in riddles: The Panama Papers and the global financial services sector. Issue 1 (12th March 2018) - Cloke, Jonathan; Brown, Ed
Abstract : In 2007, on the cusp of the economic crisis, a paper was published in Growth and Change (June 2007) entitled "Shadow Europe: alternative European financial geographies, " which began to tackle the idea of shadow finance in Europe and the size and inseparability of what was regarded as "shadow" from "normal" financial flows. A number of the observations made have proved remarkably prescient and one particular phrase stands out in the light of the recent revelations about the so‐called Panama Papers in 2016: "Strategically important flows of capital derived from complex underground production systems that have seldom been analyzed in detail move through the European financial networks that connect to offshore tax havens (Christensen, 2003). These havens are not a separate and distinct entity from the financial networks that connect world cities but rather a vital counterpart on which the functioning of the cities connected via those networks depends" (2007, p. 319). The revelation of the Panama Papers constitutes a new critical juncture from which to re‐visit that 2007 paper and to re‐examine the state of knowledge on shadow and formal financial flows.